FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI KRIM EKSTRAK ETANOL HERBA SELEDRI (Apium graveolens L.) TERHADAP BAKTERI Staphylococcus aureus - Clements, Garry; Yamlean, Paulina V. Y.; Lolo, Widya Astuty (PHARMACON, 2020)
ABSTRACTCelery herbs (Apium graveolens L.) have content flavonoid, saponin and tannin. Flavonoids have anti-inflammatory properties, antioxidants and antibacterials. This study aims to determine whether the ethanol extract of celery herbs can be formulated into cream preparations, test the quality of preparations at concentrations of 5%, 10% and 15%. These methods of research are experimental laboratories by making the supply of self-sustaining herbal celery ethanol extract cream and testing the quality of the cream preparation,  as well as testing of antibacterial activity was carried out using the liquid dilution method and measuring value of  Minimum Inhibitory Concentration  and Minimum Bactericidal Concentration using a UV-Vis Spectrophotometer. This research shows that celery herbs ethanol extract can be formulated into cream preparations, fulfilling quality test of organoleptic, scatter power, adhesion and cycling test, but that doesn’t meet the requirements for homogeneity tests and pH tests and has antibacterial activity which not only inhibits but kills bacteria in preparations of 5% and 15%Keywords: Cream Celery herb extract, Antibacterial, Staphylococcus aureus, UV-Vis spectrophotometer ABSTRAK Herba Seledri (Apium graveolens L.) memiliki kandungan flavonoid, saponin dan tannin. Flavonoid memiliki khasiat sebagai antiinflamasi, antioksidan dan antibakteri. Penelitian ini bertujuan untuk mengetahui apakah ekstrak etanol herba Seledri dapat diformulasikan menjadi sediaan krim, menguji mutu sediaan pada konsentrasi 5%, 10% dan 15%. Metode penelitian ini experimental laboratorium dengan membuat Sediaan Krim Ekstrak Etanol Herba Seledri dan menguji mutu sediaan krim, serta   menguji aktivitas antibakteri menggunakan metode dilusi cair dan mengukur nilai KBM dan KHM menggunakan Spektrofotometer UV-Vis. Hasil penelitian menujukkan bahwa ekstrak etanol herba Seledri dapat diformulasikan menjadi sediaan krim, memenuhi uji mutu sediaan organoleptik, daya, sebar, daya hambat dan stabilitas  namun tidak memenuhi persyaratan untuk uji homogenitas dan uji pH serta mempunyai aktivitas antibakteri yang membunuh bakteri pada sediaan berkonsentrasi 5% dan 15%.Kata Kunci : Krim Ekstrak herba Seledri, Antibakteri, Staphylococcus aureus, Spektrofotometer UV-Vis